Countering criminal politics arrangements in Latina America: an exploratory analysis through six cases - Rosas, Adriano Bastos (2025)
This thesis investigates the nexus between high-level corruption and organized crime in Latin America through the emerging framework of criminal politics. Building on literature on grand corruption and criminal governance, it highlights the neglected role of public sanctioningcitizen awareness, protest, and electoral punishmentin shaping collusive bargains. The first paper provides a systematic literature review, tracing the evolution from Transparency Internationals metrics and Klitgaards classical corruption model to recent notions such as power crime, criminal governance, and criminal politics. It argues for an integrated framework in which rents, institutional incentives, and public sanctions interact dynamically, alongside international pressure, to explain the resilience or collapse of criminal-political arrangements. The second paper applies this framework through six process-traced case studies: Genaro García Luna (Mexico), Juan Orlando Hernández (Honduras), Roxana Baldetti (Guatemala), Horacio Cartes and Érico Galeano (Paraguay), and Celso Gamboa Sánchez (Costa Rica). Using diagnostic tests (hoop, smoking gun, and straw-in-the-wind), the analysis shows that while protests and domestic reforms increase reputational costs, they rarely suffice to break entrenched collusion. Instead, decisive accountability usually follows international enforcementindictments, sanctions, and extraditionswhile domestic institutions prove effective only when insulated by hybrid arrangements such as Guatemalas CICIG. The findings advance theory and policy by proposing a triadic model of accountabilitypublic sanctioning, institutional capacity, and international pressurewhose interaction determines the durability or breakdown of criminal-political pacts. The thesis thus refines the concept of criminal politics and underscores the importance of hybrid accountability regimes that combine domestic transparency with robust external enforcement to counter elitecriminal collusion.